Improving the performance of community health workers in Swaziland: findings from a qualitative study - Geldsetzer, Pascal; De Neve, Jan-Walter; Boudreaux, Chantelle; Bärnighausen, Till; Bossert, Thomas John (Human resources for health, 2017)
The performance of community health workers (CHWs) in Swaziland has not yet been studied despite the existence of a large national CHW program in the country. This qualitative formative research study aimed to inform the design of future interventions intended to increase the performance of CHW programs in Swaziland. Specifically, focusing on four CHW programs, we aimed to determine what potential changes to their program CHWs and CHW program managers perceive as likely leading to improved performance of the CHW cadre.
Gesehen am 17.12.2020